2022
DOI: 10.1186/s12936-022-04201-x
|View full text |Cite
|
Sign up to set email alerts
|

Global water quality changes posing threat of increasing infectious diseases, a case study on malaria vector Anopheles stephensi coping with the water pollutants using age-stage, two-sex life table method

Abstract: Background Water pollution due to uncontrolled release of chemical pollutants is an important global problem. Its effect on medically important insects, especially mosquitoes, is a critical issue in the epidemiology of mosquito-borne diseases. Methods In order to understand the effect of water pollutants on the demography of Anopheles stephensi, colonies were reared in clean, moderately and highly polluted water for three consecutive generations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Anopheles stephensi Liston is a malaria vector mosquito that originated in Asia and the Middle East [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and recently spread to the Horn of Africa and other African countries [ 12 , 13 , 14 , 15 ]. Different from other African malaria vector species, it occurs in urban areas where artificial containers are utilized as larval habitats [ 16 ]. Therefore, it is seriously concerned that it may cause the spread of malaria in urban areas or some other environments where malaria infection is not serious [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anopheles stephensi Liston is a malaria vector mosquito that originated in Asia and the Middle East [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and recently spread to the Horn of Africa and other African countries [ 12 , 13 , 14 , 15 ]. Different from other African malaria vector species, it occurs in urban areas where artificial containers are utilized as larval habitats [ 16 ]. Therefore, it is seriously concerned that it may cause the spread of malaria in urban areas or some other environments where malaria infection is not serious [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other researchers reported that if the value of “ R” is greater than 1, the population of the species increases. They further reported that when the value of “ R” is equal to 1, the population of the species remains stable and when this value is less than 1, the population declines and the species goes extinct 44 , 45 . When the quantity of some diet ingredients in Diet 2 was increased (Diet 3) and fed it to larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus, An. stephensi is often a container-breeder which oviposits in all kind of water and thrives in urbanized settings (Walker and Lynch, 2007; Hume et al ., 2007; Tadesse et al ., 2019; Fazeli-Dinan et al ., 2022). Vector surveillance at the point of entry must target dispersal routes on a global and continental scale, but also on a local scale (Swan et al .…”
Section: Discussionmentioning
confidence: 99%